Health communications addressed to the maya from Yucatan peninsula (Mexico) within COVID-19 pandemic context - Conde-Ferráez, Laura; Andueza Pech, María Guadalupe; Gómez Carballo, Jesús Gilberto; Kantún Moreno, Nuvia; González-Losa, María del Refugio (Revista Española de Comunicación en Salud, 2022)
Introduction: Public instances use indigenous languages in communications about COVID-19; but the availability of such materials is still very limited and sometimes are not accessible enough. Objective: To generate health communications according to the reality of the most numerous indigenous group in Mexico, the maya. Methodology: We conformed a multidisciplinary working team, and to identify the necessities of information, we performed a search for official materials and a survey in Mayan communities. We generated and adjusted the communications considering linguistic and sociocultural conditions. Results: All products were spoken in maya because the majority of maya speakers do not read in their language. We generated three videos and a podcast series of six episodes, in digital format and for traditional radio. They include general health information and topics with limited coverage in maya language. Conclusion: With our communication materials, we expect to contribute to equity in information about COVID-19 and to make more visible the importance of maya language in health messages.
Keywords: health communication; COVID-19; health promotion; health of indigenous peoples